1975
DOI: 10.1016/0025-5408(75)90177-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microstructure on the dielectric properties of lanthana substituted PbTiO3 and Pb (Zr, Ti) O3-ceramics

Abstract: The effect of grain size on unit-cell dimensions and dielectric properties has been studied in ceramic lanthanasubstituted leadtitanate and leadtitanate-zirconate mixed crystals of the general composition Pbl-exLaxZryTil_y O3+x(1.5-~). The influence of grain size has been investigated in the range from 0.6~m-10~m and can be distinguished from other microstructural influences by its effect on dielectric properties. A decrease of the grain size leads to a decrease of the maximum of the dielectric constant e' at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…As the domain formation is suppressed in low grain size ceramics, the remaining stress increases with decreasing grain size. 49 The result of internal stress is a deformation of the crystal structure 25 and thus the stability of the phases may be affected. 10 Randall et al showed that internal stress in low grain size niobium doped PZT ceramics causes a deformation of the tetragonal unit cell.…”
Section: Location Of the Morphotropic Phase Boundarymentioning
confidence: 99%
“…As the domain formation is suppressed in low grain size ceramics, the remaining stress increases with decreasing grain size. 49 The result of internal stress is a deformation of the crystal structure 25 and thus the stability of the phases may be affected. 10 Randall et al showed that internal stress in low grain size niobium doped PZT ceramics causes a deformation of the tetragonal unit cell.…”
Section: Location Of the Morphotropic Phase Boundarymentioning
confidence: 99%
“…Donor and acceptor doping are used to obtain so-called ''soft'' and ''hard'' PZT materials, respectively. [3][4][5][6][7][8][9][10][11][12][13] Properties contrasting the elastodielectric properties in hard and soft PZT are given in Table I. There have been many earlier attempts to investigate the influence of grain size on the piezoelectric properties in PZT ceramics. In general, grain-size studies were limited in a range of 1.0-10 m in bulk ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of lead zirconate titanate (PZT) ceramics have been found to be considerably influenced by the variation in their microstructure particularly grain size and porosity which are dependent on the initial powder characteristics and processing parameters [1][2][3][4][5][6]. However, most of the earlier studies have been carried out using powders prepared by the ""dry" mixing technique of ball milling the constituent solid oxides by which it is difficult to provide adequate control on the powder characteristics and consequently on the microstructure and properties of the finished ceramics.…”
Section: Introductionmentioning
confidence: 99%